Treatment of diverticular disease: an update on latest evidence and clinical implications - Marilia Carabotti; Bruno Annibale (BioExcel Publishing Ltd, 2018)
Background: Diverticular disease (DD) is a common condition, especially in Western countries. In about 80% of patients, colonic diverticula remain asymptomatic (diverticulosis), while approximately 20% of patients may develop abdominal symptoms (symptomatic uncomplicated diverticular disease, SUDD) and, eventually complications as acute diverticulitis (AD). The management of this condition has been improved, and in the last five years European countries and the USA have published guidelines and recommendations. Scope: To summarize the latest evidence and clinical implication in treatment of DD focusing the attention either on the treatment of diverticulosis, SUDD and AD together with the primary and secondary prevention of diverticulitis. Findings: The present review was based on the latest evidence in the treatment of DD in the last 10 years. In the last 5 years, six countries issued guidelines on DD with differences regarding covered topics and recommendations regarding treatments. At present there is a lack of rationale for drug use in patients with asymptomatic diverticulosis, but there are limited indications to suggest an increase in dietary fibre to reduce risk of DD. To achieve symptomatic relief in SUDD patients, several therapeutic strategies with fibre, probiotics, rifaximin and mesalazine have been proposed even if a standard therapeutic approach remained to be defined. Agreement has been reached for the management of AD, since recent guidelines showed that antibiotics can be used selectively, rather than routinely in uncomplicated AD, although use of antibiotics remained crucial in the management of complicated cases. With regard to treatment for the primary and secondary prevention of AD, the efficacy of rifaximin and mesalazine has been proposed although with discordant recommendations among guidelines. Conclusion: Treatment of DD represented an important challenge in clinical practice, especially concerning management of SUDD and the primary and secondary prevention of AD.